Exploring ways to overcome barriers to mammography uptake and retention among South Asian immigrant women. (11th October 2012) - Ahmad, Farah; Jandu, Barinder; Albagli, Andrea; Angus, Jan E.; Ginsburg, Ophira
Abstract South Asians comprise one of the fastest growing immigrant groups in North America. Evidence indicates that South Asian (SA) immigrant women are vulnerable to low rates of breast cancer screening. Yet, there is a dearth of knowledge pertaining to socioculturally tailored strategies to guide the uptake of screening mammography in the SA community. In 2010, the authors conducted semi‐structured focus groups (FG) to elicit perspectives of health and social service professionals on possible solutions to barriers identified by SA immigrant women in a recent study conducted in the Greater Toronto Area. Thirty‐five health and social services staff members participated in five FG. The discussions were audio taped and detailed field notes were taken. All collected data were transcribed verbatim and thematic analysis was conducted using techniques of constant comparison within and across the group discussions. Three dominant themes were identified: (i) 'Target and Tailor' focused on awareness raising through multiple direct and indirect modes or approaches with underlying shared processes of involving men and the whole family, use of first language and learning from peers; (ii) 'Enhancing Access to Services' included a focus on 'adding ancillary services' and 'reinforcement of existing services' including expansion to a one‐stop model; and (iii) 'Meta‐Characteristics' centred on providing 'multi‐pronged' approaches to reach the community, and 'sustainability' of initiatives by addressing structural barriers of adequate funding, healthcare provider mix, inter‐sectoral collaboration and community voice. The findings simultaneously shed light on the grassroot practical strategies and the system level changes to develop efficient programmes for the uptake of mammography among SA immigrant women. The parallel focus on the 'Target and Tailor' and 'Enhancing Access to Services' calls for co‐ordination at the policy level so that multiple sectors work jointly to streamline resources, or meta‐characteristics.